Podział zysku a cash flow w zrównoważonym rozwoju przedsiębiorstw agrobiznesu - Franc-Dąbrowska, Justyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The research involved public companies operating in farm and food industry listed on the Warsaw Stock Exchange in the years 2001 -2004. The research hypothesis about low extent of cash disbursements from profits in cash flow statement was positively confirmed. It was concluded that the majority of agribusiness enterprises were taking decisions to reinvest profits. In one third of companies cash was disbursed as dividends, bonuses, and perks for employees. These companies were characterized by better then average profitability ratios and higher levels of liquidity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 329-336